Integrating Policy, Public Opinion, and Sundanese Values for Effective Public Leadership and Good Governance - Bekti, Herijanto; Pancasilawan, Ramadhan; Komara, Syifa Rachmania; Achmad, Willya (NAJAHA, 2025)
Effective public leadership is pivotal for achieving transparent, accountable, and responsive governance. This study examines the process of public leadership in implementing good governance in West Java Province by exploring the interplay of policy innovation, public opinion, and local Sundanese cultural values. Employing a qualitative case study approach across several administrative regions, data were collected through in-depth interviews, observations, and document analysis. This study finds that effective public leadership in West Java emerges from the dynamic integration of policy innovation, public opinion, and Sundanese cultural values, which collectively enhance transparency, accountability, and participatory governance. Leaders who internalise cultural principles like “Parigeuing, Dasa Pasanta, and Silih Asih” implement innovative and responsive governance mechanisms and achieve higher public trust and more sustainable policy outcomes. Effective public leadership in a culturally rich context like West Java requires a hybrid model that combines technical governance skills with cultural literacy, ethical practices, and citizen engagement to achieve good governance. Nevertheless, the research provides valuable insights for policymakers, public administrators, and scholars on culturally grounded, innovative, and citizen-centred governance strategies. Originality lies in combining the analysis of policy innovation, public opinion, and indigenous cultural values to understand effective public leadership in a specific Indonesian context, highlighting a modern, participatory, and locally rooted governance model.